2016
DOI: 10.1186/s10194-016-0630-0
|View full text |Cite
|
Sign up to set email alerts
|

Progressive muscle relaxation reduces migraine frequency and normalizes amplitudes of contingent negative variation (CNV)

Abstract: BackgroundCentral information processing, visible in evoked potentials like the contingent negative variation (CNV) is altered in migraine patients who exhibit higher CNV amplitudes and a reduced habituation. Both characteristics were shown to be normalized under different prophylactic migraine treatment options whereas Progressive Muscle Relaxation (PMR) has not yet been examined. We investigated the effect of PMR on clinical course and CNV in migraineurs in a quasi-randomized, controlled trial.MethodsThirty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 37 publications
3
42
0
5
Order By: Relevance
“…CNV normalization during migraine attacks has been reported. Before PMR-training, migraine patients exhibited higher amplitude iCNV and overall CNV (oCNV) than seen for healthy controls, but no differences in habituation occur (Meyer et al, 2016). Additionally, there is no significant difference in CNV amplitude or habituation in patients with migraine during an attack period when compared with a control group.…”
Section: Introductionmentioning
confidence: 90%
“…CNV normalization during migraine attacks has been reported. Before PMR-training, migraine patients exhibited higher amplitude iCNV and overall CNV (oCNV) than seen for healthy controls, but no differences in habituation occur (Meyer et al, 2016). Additionally, there is no significant difference in CNV amplitude or habituation in patients with migraine during an attack period when compared with a control group.…”
Section: Introductionmentioning
confidence: 90%
“…In a study involving 35 patients with migraine and 46 healthy controls, six-week PMR-training was performed to 16 patients with migraine and 21 healthy controls, who were then compared using contingent negative variation (CNV) measurements to investigate cortical information. In conclusion, although no meaningful difference between patients with migraine and healthy controls were identified in CNV measurements, there was a decrease in the monthly frequency of headaches and the number of days with headache in the migraineurs after the PMR training (11). Studies on PMR have revealed a decrease in headache frequency and days with headache in migraineurs.…”
Section: Relaxation Techniquesmentioning
confidence: 63%
“…So kann die Umlenkung der Aufmerksamkeit auf nicht schmerzassoziierte Erlebnisinhalte im Sinne einer Ablenkung zu einer höheren Schmerztoleranz und verbesserten Schmerzbewältigung beitragen, was in Schmerzbewältigungstrainings und teilweise auch Entspannungstechniken angewandt wird. Psychophysiologische Forschung [21]…”
Section: Hin Zu Einer Kopfschmerzpsychotherapieunclassified